United States Poverty in a Cross-National Context - Timothy M. Smeeding; Lee Rainwater; Gary Burtless (Luxembourg Income Study (LIS), 2000)
In this paper we use cross-national comparisons made possible by the LIS to examine America's experience in maintaining a low poverty rate. We compare the effectiveness of United States antipoverty policies to that of similar polices elsewhere in the industrialized world. If lessons can be learned from cross-national comparisons, there is much that can be learned about antipoverty policy by American voters and policymakers. The United States has one of the highest poverty rates of all the countries participating in the LIS, whether poverty is measured using an absolute or a relative standard for determining who is poor. Although the high rate of relative poverty in the United States is no surprise, given the country's well-known tolerance of wide economic disparities, the lofty rate of absolute poverty is much more troubling. After Luxembourg, the United States has the highest average income in the industrialized world. Our analysis of absolute poverty rates provides poverty estimates for 11 industrialized countries. The paper is organized as follows. We begin by reviewing international concepts and measures of poverty as they relate to the main measures of income and poverty used in other chapters of this book. Next we present cross-national estimates of both absolute and relative poverty, concentrating on the latter measures. After examining the level and trend in these rates, we explore some of the factors that are correlated with national poverty rates and examine the antipoverty effectiveness of government programs aimed at reducing poverty. We conclude with a discussion of the policy differences and outcome differences we find, and we consider the implications of our analysis for antipoverty policy in the United States.
Keywords: 330; Armut; Vergleich; USA; OECD-Staaten